Interest Rate Movements on Stock Market Performance: A Focus on Private Sector Banks (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: The study investigates the relationship between interest rate fluctuations and stock market performance with a specific focus on private sector banks in India. Interest rates, being a crucial monetary policy instrument, directly influence capital costs, borrowing patterns, and investment decisions. Private sector banks, being highly sensitive to economic and financial changes, serve as an ideal sector to explore these dynamics. This research aims to examine both the short-term and long-term effects of interest rate changes on private sector bank stock prices, trading volumes, and investor sentiment. It also compares the responsiveness of private sector bank stocks with overall market indices. The study employs econometric techniques using secondary data on interest rates, stock prices, and market indices. Findings are expected to provide valuable insights for investors, policymakers, and financial institutions on managing risks and formulating strategies in the face of interest rate volatility.